Future potential country doctor: the perspectives of German GPs - Natanzon, Iris; Szecsenyi, Joachim; Ose, Dominik; Joos, Stefanie (Rural and remote health, 2010)
INTRODUCTION - There is a shortage of general practitioners (GPs) in many countries, especially in rural areas. There are several reasons for this shortage. Over the last decade, fewer medical students in Germany have decided to work in patient care, even fewer in general practice and fewer still in general practice in rural areas. The aim of this study was to explore the 'pros and cons' of GPs' work in rural areas and to identify from GPs' perspective possible measures for counteracting future GP shortages. - METHODS - Within a qualitative approach, 16 semi-structured interviews were conducted with GPs. Data analysis was carried out using qualitative content analysis. - RESULTS - The results were categorized into three main inductively-derived categories: personal, professional and regional/structural level. A higher level of self-confidence and a higher 'feel-good' factor due to GPs originating from rural areas were positive aspects at the personal level. Regarding the professional level, a low level of competition and varied work made a GP's profession attractive in rural areas. Negative aspects were mostly apparent at the regional/structural level, such a low earnings and few leisure facilities. Measures to counter the lack of GPs in rural areas were explored on all three levels: on the personal level, more optimism and resulting satisfaction on the part of doctors in rural areas could be improved by enhancing the benefits of being a doctor in a rural area. Regarding the professional level, more group practices are required to make working as a GP in a rural area more attractive. At a regional/structural level, young physicians who originate from rural areas should be recruited to work in rural areas. - CONCLUSIONS - Financial incentives are regarded as not sufficient to attract enough young physicians to open practices in rural areas. Future action will be required at the personal, professional and regional/structural levels. The origin of medical students (urban or rural) should be considered a relevant predicting factor for recruitment.